The Effect of Technostress on Turnover Intention with Burnout as a Mediation in Gen Z in the City of Surabaya - Nanda Putri Kandita; Sarwari Sarwari; Galuh Ajeng Ayuningtiyas; Priyanto Priyanto (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
Using burnout as a mediating variable, this study looks at how technostress affects turnover intention among Gen Z workers in Surabaya. Based on the city's rapid digitization and widespread internet access, the study examines how technological advances can boost productivity and create difficulties associated with technology use. Technostress is defined as an unpleasant psychological state that results from a person's inability to adapt to the demands and advances of technology. Burnout, a condition of physical, emotional, and mental exhaustion brought on by ongoing job stress, is said to be the result of this strain for Gen Z, often known as